Modelagem matemática e análise de desempenho da hibridização de motores Stirling operando com biogás e energia solar no Brasil - Bryan Castro Caetano (2023)
Currently, both the agricultural sector and the electricity production sector are major sources of greenhouse gas emissions. Concerns about sustainability and especially environmental risks related to climate change have influenced the development of new technologies for power production. Because they have external combustion, Stirling engines can operate with a wide variety of heat sources. Therefore, its use and hybridization has been the object of study in several studies. The use of biogas and solar energy presents an interesting alternative for the use of cleaner energy, which can be used in regions far from conventional production and distribution centers, such as rural properties, which represents an environmentally appropriate form of bio treatment, waste and use of renewable sources. To prove the potential of hybridization of these heat sources, the present work aims to evaluate the technical feasibility of implementing a Stirling engine operating with heat from concentrated solar energy and the burning of biogas produced in biodigesters with livestock waste. A mathematical model is developed to estimate the performance of the hybrid system, which combines the modeling of the Stirling engine, the concentrator disc, the burner and the biodigester. The model is tested using boundary conditions similar to the conditions that the system would be subjected to if operating in Brazil. The engine map is constructed by calculating the engine's power output, the amount of heat required and its thermal efficiency for different speeds and heating temperatures. The part of the system that concentrates and collects solar radiation is evaluated by operating in the cities of Ourinhos-SP and Natal-RN and using concentrator disks with different sizes. The burner performance is evaluated for different geometries and biogas mixtures. The influence of the type of biomass inserted in the biodigester on the number of animals, daily water consumption and volume of the biodigester is evaluated for continuous operation of the hybrid system. The results presented show that hybridization with solar energy can reduce biogas consumption by 30%. On the other hand, the use of biogas reduces fluctuations in power production using only solar energy and allows constant operation. Considering the moments of lower available solar radiation, there were no significant variations in the number of animals required when comparing the system operating in Ourinhos and Natal. Furthermore, the number of animals needed to operate the hybrid system proved to be feasible in the Brazilian scenario, for example, 20.9 and 20.1 pigs are needed for constant production of 1kW in the cities of Ourinhos and Natal, respectively. Therefore, the hybridization of Stirling engines using solar energy and biogas produced from agro-industry waste, as proposed in this work, has great potential for operation in a country like Brazil, which is privileged in the incidence of solar radiation and has one of the largest agro-industry. of the world.